The Effectivenes of Minidiorama Media on the Student’s Learning Motivation in Theme Cita-Citaku - Silviana Nur Faizah; Ummu Khairiyah (MODELING: Jurnal Program Studi PGMI, 2020)
Minidiorama media is a miniature learning media that is equipped with background, lighting, and audio. This media helps describe abstract knowledge into concrete by giving students a direct learning experience. This research used quantitative experimental approach to the design of the pre-test post-test design of one group (One Group Pre-test Post-test Design) to determine the effectiveness of minidiorama media on students’ learning motivation on the theme of sub-themes of hebatnya cita – citaku in MI Kutukan Salafiyah of Blora, amounting to 31 students. Data on student motivation was obtained using a questionnaire consisting of 15 statements on the Guttman scale. The results showed the average motivation to learn before using mindiorama media (pre-motivation) was 60 with less motivated criteria and the average motivation to learn after using minidiorama media (post-motivation) was 81 with motivated criteria.Paired samples test analysis using SPSS 25 was used to test the research hypothesis. The results of the analysis will be tested with the criteria Ha accepted and H0 rejected if Sign. <0.05, then based on the results of Sig. (2-tailed) of 0,000 <0.05 so Ha is accepted. So it is concluded that the proposed Ha is accepted, namely minidiorama media effective in increasing learning motivation on the theme of Cita - citaku, the subtheme of Hebatnya cita - citaku in Class IV MI Salafiyah Kutukan Blora.